2014
DOI: 10.1111/ecin.12060
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Experimental Wage Negotiations

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 40 publications
5
64
0
2
Order By: Relevance
“…According to this approach, women are not used to making requests on their own behalf. In line with this, many studies confirm that women submit lower wage bids (Rigdon 2012;Dittrich et al 2014).…”
Section: Discrimination From the Supply Sidementioning
confidence: 59%
“…According to this approach, women are not used to making requests on their own behalf. In line with this, many studies confirm that women submit lower wage bids (Rigdon 2012;Dittrich et al 2014).…”
Section: Discrimination From the Supply Sidementioning
confidence: 59%
“…In the same vein in the lab and in other domains, studies observe similar gender-pairing effects in ultimatum (Eckel & Grossman, 2001), dictator (Ben-Ner et al, 2004), multistage alternatingoffer bargaining (Dittrich et al, 2014), and in all-pay auction games (Chen et al, 2015). While there seems to be evidence on women's economic decision-making being affected by the gender of the party with whom they are interacting, explanations regarding women's preferences for same-gender competition are rather rare.…”
Section: Introductionmentioning
confidence: 77%
“…Negotiation practices and outcomes studied within a lab context, as simulations, have facilitated findings on the impact of salary offered and employer behavior on the perceived attractiveness of a job (Porter et al, 2004), how different training programs affect subsequent negotiation behavior (Stevens et al, 1993), whether gender differences in negotiation practice could be connected to differences in how men and women are treated when negotiating (Bowles et al, 2007), and gender differentials in negotiation behavior (Bowles et al, 2007;Dittrich et al, 2014), and pairing outcomes (Dittrich et al, 2014). Survey and interview methodologies have also been deployed to study the reported experiences and outcomes of actual negotiations, capturing negotiation frequency and strategy of women university administrators (Compton and Bierlein Palmer, 2009) and school psychology practitioners and faculty (Crothers et al, 2010a, b), the impact of negotiation outcomes on later job attitudes and turnover intentions (Curhan et al, 2009), assessing individual differences in negotiation behaviors and outcomes (Marks and Harold, 2011), and exploring the extent of negotiation and impact on starting salary (O'Shea and Bush, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have found that salary requests of male respondents were significantly higher and correlated with beliefs that differed from women respondents' (Barron, 2003), that female negotiators were penalized more for initiating negotiation than men (Bowles et al, 2007), that women's negotiation outcomes were worse than men's when in the role of employee, but not as the employer (Dittrich et al, 2014), that while school psychology faculty of all genders negotiated at comparable rates, women faculty reported more negative consequences as a result (Crothers et al, 2010a, b), and that recent hires of all genders negotiate at similar rates, but women saw less gains (Marks and Harold, 2011). Findings were uniformly consistent across studies; O'Shea and Bush (2002) surveyed recent college graduates to determine extent of negotiation, including gender differentials, and impact on starting salary, observing an additional average of $1,500 for those negotiating and similar propensity and success rates across gender.…”
Section: Literature Reviewmentioning
confidence: 99%